GIS Based Satellite Image Denoising Using Curvelet Transform - S. Sinthuja; Santhosh Saravanan (Institute of Advanced Engineering and Science, 2017)
Generally, satellite images contain very significant information about geographical features such as rivers, roads, building and bridges etc of the earth. Geographic Information System (GIS) requires these features for automatic detection and it has been corrupted by various types of noise. Curvelet Transform (CT) is used in the proposed system for denoising the images. Advantages of multi resolution image such as line, compatibility of human visual system and edge detection are provided. Then K-Means clustering is used in this system for segmentation purpose after the pre processing done.First, K-Means algorithm is used for segmenting background and water then extraction of bridges is done based on pixel intensity difference.